IMPACT OF THE TRAINING PROGRAM OF THE PHILIPPINE TRAINING CENTERS FOR RURAL DEVELOPMENT ON FARMER MODERNITY - Goltiano, Henry Y.; Castillo, Gelia T. (Annals of Tropical Research, 1989)
This study assessed the impact of PTC-RD training on farmer moder-nity. It specifically determined whether or not there were significant differ-ences in modernity among three comparison groups that represented a continuum of training experience: the never-trained, slightly-trained and highly-trained farmers. There were 61 respondents whose personal, family and occupational characteristics did not differ significantly. Twenty respondents had never attended a PTC-RD training, 27 were trained only once, and 14 thrice or more. An interview schedule was developed to gather data and information from the respondents. Based on the Wilcoxon Rank-Sum test of difference in means, the three groups of respondents significantly differed in active public participation, efficacy, occupational aspirations, planning valuation, technol-ogy valuation and time valuation. The highly-trained respondents proved to be the most modern among the three groups.